2009
DOI: 10.1177/0269216309102987
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of palliative care emergencies by prehospital emergency physicians in Germany: an interview based investigation

Abstract: Palliative care medical emergencies as a consequence of advanced cancer account for approximately 3% of all prehospital emergency cases. Therefore, prehospital emergency physicians (EP) are confronted with 'end of life decisions'. No educational content exists concerning palliative medicine in emergency medicine curricula. Over the course of 6 months, we interviewed 150 EPs about their experiences in 'end of life decisions' using a specific questionnaire. The total response rate was 69% (n = 104). Most of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
15

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 13 publications
1
32
0
15
Order By: Relevance
“…A study by Mercadante et al (9) on palliative care patients reported that even phone consultations or intervention with a palliative care unit helps to reduce hospital admissions. In another study, it was stated that having a palliative care team reduces unnecessary ED admissions (10). Therefore, it is important for a hospital to establish a separate palliative care unit in order to respond to cancer patients' needs more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Mercadante et al (9) on palliative care patients reported that even phone consultations or intervention with a palliative care unit helps to reduce hospital admissions. In another study, it was stated that having a palliative care team reduces unnecessary ED admissions (10). Therefore, it is important for a hospital to establish a separate palliative care unit in order to respond to cancer patients' needs more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced training in palliative care medicine and end-of-life care should be integrated into emergency medical training. 3,4,8,11 It has been reported that patients seem to favor continuity of care and admission to an oncology ward directly. 12 As an alternative, a team of hospice nurse specialists, acting at the request of a well-recognized emergency system, can provide a concrete and useful response to problems of unwanted hospitalization in acute emergencies for home-based terminally ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this usually concern legal uncertainties and unknown advance directives. 3,8,10 In Italy, it is unusual to provide advance directives. Of interest, there is a risk that any advance directive may not be taken into consideration according to a new law, which is being discussed and examined in the Italian Parliament.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations